A dictionary of world mythology - Cotterell, Arthur (Oxford [Oxfordshire] : Oxford University Press, 1986)
Highlights the chief myths of the world in seven main sections--West Asia, South and Central Asia, East Asia, Europe, Africa, America, and Oceania.
Includes index.
Bibliography: p.
Adult
Keywords: Mythology -- Dictionaries; Mythology -- Dictionaries